Mary D'Alimonte, Case Study, "How Evidence Informs Decision-Making: The Scale-Up of Nutrition Actions Through an Early Childhood Development Platform in Malawi" - D'Alimonte, Mary (2019)
Mary D'Alimonte POLICY SEMINAR Using Malawi’s Community-Based Childcare Centers to Implement an Agriculture and Nutrition Intervention Co-organized by IFPRI, the University of Washington led SEEMS nutrition project, and the CGIAR Research Program on Agriculture for Improved Nutrition and Health (A4NH)